The Impact of Cultural Heritage on Coexistence Relations in a Local Community - Henriett Szabó (Különleges Bánásmód)
The analysis of community processes in peripheral local rural societies is usually described in terms of assimilation, integration and segregation. The basic motivation for the research presented in this paper was that, in my experience, the integration processes of the largest ethnic minority in Hungary can only be fully comprehended if the autonomous narratives of local communities concerning their own life situations are acknowledged as interpretations that underpin our conclusions. A field study was conducted using ethnographic and anthropological methods in two settlements in Hajdú-Bihar County. The aim was to investigate the impact of the structure of the Gypsy subcommunity's traditional heritage, its recurrent functions and the emerging revival processes on coexistence. I was looking for an answer to the question whether the traditional practices of the Roma, the use of language, the set of customs, the ethnic norms help or hinder social integration. This paper presents the results and conclusions of a research conducted in one of the settlements, in Nagyrábé. The objective of the research was to identify the factors that influence the social acceptance of local Roma communities and examine their relation to the quality of the preservation of ethnic traditions.